Betting on failure : profiting from defaults on subprime mortgages - Furfine, Craig ([London] : SAGE, 2016)
In October 2008, in the midst of a financial crisis, Anthony Keating, investment manager at the Boston private bank Billingsley, Blaylock, and Montgomery, was searching for an investment strategy to recommend to his high-net-worth clients. Traditional investments in the equity markets were being decimated, and Keating's clients would be looking to him for ideas. Inspired by the success of Paulson and Co., Keating began to explore the possibility of entering a trade that would profit as homeowners defaulted on their mortgages. This case study explains his methods.
Originally Published in: Furfine, C. (2015). Betting on Failure: Profiting from Defaults on Subprime Mortgages. 5-312-504. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Secondary mortgage market -- Case studies; Mortgage-backed securities -- Case studies; Subprime mortgage loans -- Case studies